REVIEW OF THE LITERATURE ON THE USE OF PROBLEM-BASED LEARNING MODELS IN CHEMISTRY EDUCATION AND THEIR OUTCOMES - Raula Saputri, Legendaria; Syahidatul Nisa, Lilis; Rahmawan, Setia (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
The instructor must employ a learning model to assist the material's exposition during the teaching process. Poor learning results for students are primarily a result of teacher quality. Where teachers continue to exert much control over the learning process and do not apply cutting-edge teaching techniques. The goal of this study is to conduct a literature review on papers that examine the chemistry learning outcomes using problem-based learning model. This analysis used a total of twenty scholarly publications from Google Scholar between 2020 and 2024. A table listing published scientific articles analyzed in the research data is used as the data presentation strategy. Scientific articles were identified and analyzed to generate a descriptive data analysis technique.